Katophorite from the Jade Mine Tract, Myanmar: mineral description of a rare (grandfathered) endmember of the amphibole supergroup. (2nd January 2018) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank C.; Ball, Neil A.; Harlow, George E.
Abstract: Katophorite has the ideal formula A Na B (NaCa) C (Mg4 Al) T (Si7 Al)O22 W (OH)2 (Hawthorne et al., 2012). No published analyses of amphiboles fall in the katophorite compositional field, except that of Harlow and Olds (1987) for an amphibole from near Hpakan in the Jade Mine Tract, Myanmar. This amphibole was approved by the International Mineralogical Association Commission on New Minerals, Nomenclature and Classification (vote 2013-140) as katophorite, and is reported here. Holotype katophorite is monoclinic, space group C 2/ m, a = 9.8573(8), b = 17.9617(15), c = 5.2833(4) Å, β = 104.707(2)°, V = 904.78(13) Å 3, Z = 2. The calculated density is 3.091 g cm –3 . In plane-polarized light, katophorite is pleochroic, X = pale blue (medium), Y = light blue-green (strongest), Z = colourless; X ∧ a = 30.6° (β obtuse), Y || b, Z ∧ c = 15.8 (β acute). It is biaxial negative, α = 1.638, β = 1.642, γ = 1.644, all ± 0.002; 2Vobs = 73(1)°, 2Vcalc = 70°. The eight strongest lines in the powder X-ray diffraction pattern are [ d in Å ( I )( hkl )]: 2.700 (100)(151), 3.129 (69)(310), 2.536 (65)(202), 3.378 (61)(131), 8.421 (55)(110), 2.583 (46)(061), 2.942 (43)(221) and 2.334 (41)(351). Electron-microprobe analysis of the refined crystal gave SiO2 51.74, Al2 O3 7.38, TiO2 0.14, FeO 1.55, Fe2 O3 2.82, MgO 18.09, CaO 8.17, Na2 O 6.02, K2 O 0.24, F 0.06, H2 Ocalc. 1.80, Li2 Ocalc. 0.09, sum 100.55 wt.% (Li2 O and H2 O based on the results of single-crystal structure refinement). The formula unit, calculated on the basis of 24 (O, OH, F) with (OH + F + O) = 2 is: A (Na0.85 K0.04 )Σ=0.89 B (Ca1.22 Na0.78 )Σ=2.00 C (Mg3.76 Al0.43 Fe0.30 3+ Cr0.27 3+ Fe0.18 2+ Li0.05 Ti0.01 4+ )Σ=5.00 T (Si7.21 Al0.79 )Σ=8.00 O22 W [(OH)1.67 O0.30 F0.03 )]Σ=2.00 .